Primary Peritoneal Serous Carcinoma with Coexistent Mucinous Cystadenoma of Ovary – A Rare Case Report - Rajashree Pradhan; Sajeeb Mondal; Upasana Mukherjee (Journal of Mid-Life Health)
Primary peritoneal serous carcinoma (PPSC) is an extremely rare tumor mostly idiopathic in nature arising from the peritoneal layers of the abdominal cavity. We present here a unique case of a 72-year-old female with a history of abdominal swelling and difficulty in micturition and defecation for 3 months. Diagnostic imaging and histopathological examinations led to the diagnosis of PPSC. Simultaneously, the patient also has a space-occupying lesion involving the left ovary which on histopathological examination was found to be mucinous cystadenoma. We present this case as PPSC with synchronous mucinous cystadenoma of the left ovary, an extremely rare phenomenon. This combination has not been reported in the literature yet to the best of our knowledge.